Language Learning Strategies Used by Santri During Pesantren Speech Program for Developing their Speaking Ability - Isyqi Amaliyah; Mursid Saleh (English Education Journal, 2022)
Using two languages, Arabic and English, at the same place and taking turns time, is one of the problems faced by some santri at Islamic boarding schools or pesantren. This study aimed at investigating the impact of English language learning strategies used by santri during the pesantren speech program on their speaking ability. This study applied a qualitative approach, specifically case study design. Observation, interview, and documentation were conducted to collect the research data. Also, the theory of language learning strategies by Oxford (2013) was used for analyzing the research data. The result of this study showed that the 12 participants used all types of language learning strategies, namely 1) memory strategies, 2) cognitive strategies, 3) compensation strategies, 4) metacognitive strategies, 5) affective strategies, and 6) social strategies. The percentage showed that 92% of the santri used memory strategies, 50% used cognitive strategies, 17% used compensation strategies, 75% used metacognitive strategies, 33% used affective strategies, and the last 100% of santri used social strategies in pesantren speech activity. All participants in this study stated that speech activities at Islamic boarding schools positively enhanced their speaking ability. It can be seen when they deliver speeches in front of an audience. They can improve their spoken language more than the text they made before. Thus, it can be concluded that speech programs could positively improve students’ speaking skills.